Physio-chemical interaction of Ethylene-Vinyl Acetate copolymer on bonding ability in the cementing material used for oil and gas well - Lanka, S.T. (KeAi Publishing Communications Ltd., 2021)
Effective bond of cement sheath to casing or formation depends on higher tensile strength and lower young's modulus which are a measure of its ability to withstand deformation under load without parting. This work utilized Ethylene Vinyl Acetate (EVA) redispersible polymer powder as additive in the class G cement to characterize bonding ability. Tensile strength was measured for samples cured at 90 Â°C for 3 days, whereas compressive strength was measured for samples cured at 120 Â°C for 1 day and 3 days under atmospheric pressure. The results showed that, with the addition of beyond 10 by weight of cement (BWOC) of polymer, not only tensile strength was improved, but also reduced young's modulus. Addition of EVA additive beyond 10 BWOC showed significant benefit of flexibility in the cement system. FTIR (Fourier Transform Infrared Spectroscopy) indicated that presence of high VA (Vinyl Acetate) has no effect on polymerization of Silicates, which shows it does not hider in the formation of CâSâH phase. Intensity of chemical bond augmented with longer curing time and increased polymer content, as seen in OâH stretching vibration at 3434 cmâ1 and from Carboxylate anion at 1571 cmâ1 to confirm on hydrolysis. Mercury Intrusion porosimeter (MIP) showed significant reduction in fraction of mesopore sizes within the cement matrix, with the polymer addition. Â© 2021 Chinese Petroleum Society